(untitled) (The Agriculturists, 2016)
The tandem repeats, conserved short segments of DNA, which are found in all prokaryotic and eukaryotic genomes, are called microsatellites. It is also known as variable number tandem repeats (VNTRs), simple sequence repeats (SSRs) and short tandem repeats (STRs). Microsatellites present in both coding and non-coding regions of a genome. The high polymorphism of microsatellites makes them powerful genetic markers for genome mapping of many organisms. It is also suitable for ancient and forensic DNA studies for population genetics and conservation of biological resources. The major disadvantage of microsatellites is that for the first time they need to be isolated de novo from most species being examined. The task of microsatellite isolation is quite cumbersome involving in terms of effort and time, because it traditionally involves screening of genomic libraries. Cross-species amplification, Mining microsatellites from nucleotide sequenced data and Genomic library- based method are general methods of microsatellite isolation. Cross-species method may not effective for all species, Data mining is not applicable if there is no or limited data of DNA sequence. Genomic library based method is the best choice. Traditional protocol, primer extension protocol, selective hybridization, and Fast Isolation by AFLP of Sequences containing repeats (FIASCO) are the protocols of microsatellite development based on genomic library. FIASCO is the best protocol ever developed. The Agriculturists 2015; 13(1) 152-172